Diseño e implementación de una solución de telefonía móvil para la red UMTS en la avenida perimetral Simón Bolívar en la ciudad de Quito para brindar cobertura y calidad - Cuichán Cueva, Ricardo Javier (2016)
The Simon Bolivar Avenue is located in the canton QUITO, this crosses a topography of mountainous terrain, so the nodes prior to project implementation does not provide coverage in its entirety, being an avenue with high number of users who demand voice service and data the project is implemented to improve the coverage and quality of the UMTS network using WCDMA / HSDPA + technology, which will allow its users to have continuity services. A first drive test is performed to measure parameters of RSCP and Ec / Io and status outcomes coverage and network quality in the Simon Bolivar Avenue is obtained from the section of Llano Chico to Tambillo. With nominal data points (coordinates) are located, with the use of global positioning software (Google Earth). types of antennas, azimuth, tilt electrical, mechanical inclination, for which the predictions and planning software will be used ATOLL: Once found and validated points nominal radio frequency parameters of each node as determined. Installed the radiant system runs one second drive test and the information obtained is processed and the parameters are analyzed: RSCP (signal received code power), Ec / Io (energy per chip and interference level), best server (cell with best levels RSCP and Ec / Io parameter), BLER (Block Error Rate), transmit power, soft handover, pilot pollution, throughput downhill modulation, CQI (Channel Quality Indicator).